The biotechnology revolution in global agriculture : innovation, invention, and investment in the canola industry (Biotechnology in agriculture series, 2001)
This book reviews the global canola sector in order to identify fundamental trends resulting from the adoption of biotechnology. It examines the sector over an extended period, looking at its local origins, regional growth and international expansion; analyses public policy affecting commercialization; and estimates the costs and benefits of changes. It is aimed at government and industry researchers and students involved in agricultural economics, plant biotechnology and crop science. It contains 17 chapters and a subject index.